Cell Wall Biogenesis Protein Phosphatase CrSsd1 Is Required for Conidiation, Cell Wall Integrity, and Mycoparasitism in Clonostachys rosea - Lv, Binna; Jiang, Na; Hasan, Rakibul; Chen, Yingying; Sun, Manhong; Li, Shidong (Frontiers in Microbiology, 2020)
Cell wall biogenesis protein phosphatases play important roles in various cellular processes in fungi. However, their functions in the widely distributed mycoparasitic fungus Clonostachys rosea remain unclear, as do their potential for controlling plant fungal diseases. Herein, the function of cell wall biogenesis protein phosphatase CrSsd1 in C. rosea 67-1 was investigated using gene disruption and complementation approaches. The gene-deficient mutant ΔCrSsd1 exhibited much lower conidiation, hyphal growth, mycoparasitic ability, and biocontrol efficacy than the wild-type strain, and it was more sensitive to sorbitol and Congo Red. The results indicate that CrSsd1 is involved in fungal conidiation, osmotic stress adaptation, cell wall integrity, and mycoparasitism in C. rosea.